Analyzing and Developing a Mobile-Based Geographical Information System - Tri Basuki, Kurniawan; Dedi, Suwanto (INTI International University, 2023)
In order to learn about job openings, candidates still rely on manual methods including going to companies and looking at job notice boards, as well as looking through print materials like newspapers, magazines, brochures, and word-of-mouth recommendations. A lot of research is being done to find out about things like the Geographic Information System (GIS), Palembang Job Openings, and Mobile Based. With the help of an information system, job hunters can quickly get comprehensive information. The Internet is a state-of-the-art telecommunications tool; thus, it is expected to make things easier for its users, which is good for job seekers and companies that are hiring. Eventually, job seekers will be able to contact recruiters and companies to post job openings through this program, which may be conveniently accessed online and created as a non-profit organization. This paper presents the analysis of mobile-based GIS requirements and the development of the system that can tackle the mentioned problem above.